2001
DOI: 10.1093/nar/29.21.4319
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana genome contains at least 29 active genes encoding SET domain proteins that can be assigned to four evolutionarily conserved classes

Abstract: SET domains are conserved amino acid motifs present in chromosomal proteins that function in epigenetic control of gene expression. These proteins can be divided into four classes as typified by their Drosophila members E(Z), TRX, ASH1 and SU(VAR)3-9. Homologs of all four classes have been identified in yeast and mammals, but not in plants. A BLASTP screening of the Arabidopsis genome identified 37 genes: three E(z) homologs, five trx homologs, four ash1 homologs and 15 genes similar to Su(var)3-9. Seven genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
320
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(330 citation statements)
references
References 61 publications
6
320
1
Order By: Relevance
“…In plants, Arabidopsis SET (AtSET) proteins are the best annotated and characterized. Baumbusch et al [44] were the first to classify 37 putative Arabidopsis SET genes into four distinct classes: 1) Enhancer of zeste [E(z)] homologs; 2) Ash1 homologs and related; 3) trithorax (trx) homologs and related; and 4) Suppressor of variegation [Su(var)] homologs and related. Subsequently, Springer et al [22] classified 32 Arabidopsis and 22 maize SET proteins into 19 orthology groups distributed among five classes according to their phylogenetic relationships and domain organization.…”
Section: Classification and Functions Of Plant Set Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…In plants, Arabidopsis SET (AtSET) proteins are the best annotated and characterized. Baumbusch et al [44] were the first to classify 37 putative Arabidopsis SET genes into four distinct classes: 1) Enhancer of zeste [E(z)] homologs; 2) Ash1 homologs and related; 3) trithorax (trx) homologs and related; and 4) Suppressor of variegation [Su(var)] homologs and related. Subsequently, Springer et al [22] classified 32 Arabidopsis and 22 maize SET proteins into 19 orthology groups distributed among five classes according to their phylogenetic relationships and domain organization.…”
Section: Classification and Functions Of Plant Set Proteinsmentioning
confidence: 99%
“…ASHH1 is the Arabidopsis homolog of yeast Set2 [44] which has been shown to exhibit H3K36 methyltransferase activity [64]. In addition, genetic studies revealed that ashh2 mutants show an early flowering phenotype that is accompanied by a decrease in H3K36 methylation at the FLOWERING LOCUS C (FLC) [65].…”
Section: Class Ii: the Ash1 Homologs (H3k36)mentioning
confidence: 99%
See 1 more Smart Citation
“…The SET domain is found in a large number of eukaryotic proteins (see pfam database) as well as in a few bacterial proteins [23] and is not limited to HKMTs. HKMTs can be classified according to the presence or absence and the nature of sequences surrounding the SET domain that are conserved within families [24,25]. Representatives of the major families include SUV, SET1, SET2, EZ, and RIZ (for example, see [26]).…”
Section: Set Domain Proteinsmentioning
confidence: 99%
“…These factors are, in many cases, remarkably well conserved in distantly related species [4][5][6][7][8][9][10]. Histone Lysine Methyl Transferases (KMTs), enzymes that add one, two or three methyl groups to lysine residues within the tails of histones, as well as proteins with chromodomains that bind specifically to motifs generated by KMTs, are the best characterized factors required for setting up heterochromatin.…”
Section: Introductionmentioning
confidence: 99%